Eficiência energética em edifícios: investigação do S3E como interface de simulação simplificada - Marina da Silva Garcia (2017)
Computer simulation is globally used to evaluate energy efficiency in buildings, but the high level of complexity found in some software often leads to a time and money consuming process. Simplified simulation tools have the potential to turn this process into a more accessible one, giving faster and more precise results compared to detailed simulations and the prescriptive method. This work aims at investigating the Web S3E interface - developed by the LabEEE at the Federal University of Santa Catarina - and its use along with RTQ-C in a case study applied to the UFMG School of Architecture (EA/UFMG). Previous works mentioning this interface were initially studied, following a practical use of the tool as well as the investigation of others simplified computational simulation software - CE3, CE³X e Atmospheres which were compared with the Brazilian tool. The case study was divided into two parts, namely EP1 and EP2. In EP1, considering the S3E regular geometric patterns limitation, the dividing blocks methodology - as in NT07 (CB3E, 2014) of the prescriptive method - was used to investigate the interface results regarding the non-regular geometry building case, as the EA/UFMG. Following the application of the prescriptive method, both in S3E and EnergyPlus, the differences in ENCEs results and energy consumption were calculated. In EP2, the energy efficiency and energy consumption classification of one of the blocks from EP1 were initially studied. Besides that, the influence of some simplifications in S3E as geometry, schedules, envelope description, openings and its shading devices, was studied regarding energy consumption and the level of energy efficiency. From the data analysis, it was noticed that S3E presented some important modifications after the publication of the previously analyzed works. They have the potential to maximize its precision, with the common principles functionalities indicating further development possibilities in the S3E platform. The EP1 results shows that the S3E calculated ENCE was equal to the one calculated with EnergyPlus. In EP2, the classification was the most permissive among the others three methods used. Considering the simplifications, it was noticed that the schedules have the bigger potential to influence in energy consumption results. Despite being a work focused in only one building, the aspiration is that it can contribute in discussions about S3E utilization as an official tool for the process of attaining an ENCE in RTQ-C.